Efficiency evaluation of service marketing in a Hungarian Telecommunication Company - Kalmár, Katalin; Kárpáti, László (Applied Studies in Agribusiness and Commerce, 2008)
It is unquestionable that marketing is an essential promotor of the economy and commerce. With its diverse tools, it can influence consumers and also regulate supply by measuring needs and demands (Bauer-Berács, 1998). Although the roots of marketing go back centuries, it is interesting that the raison d’être of service marketing was disputed even in the 1960s and 1970s. However, by today it has developed into a substantive specialty. In this study, the inquiry service and the implemented marketing tools of a leading Hungarian telecommunications company were studied for four years. (The data was provided by the communication manager of the company. Being bound to secrecy, I will not disclose the name of the company or the inquiry service.)